Correlates of Glycemic Control Among Patients With Type 2 Diabetes in Eastern Ethiopia: A Hospital-Based Cross-Sectional Study - Letta, Shiferaw; Aga, Fekadu; Yadeta, Tesfaye Assebe; Geda, Biftu; Dessie, Yadeta (Frontiers in Endocrinology, 2022)
Introduction: Optimal blood glucose control prevents diabetes-associated complications. However, a significant proportion of patients with Type 2 diabetes (T2D) fail to attain optimal glycemic control due to many reasons. Therefore, this study aimed to find out the correlates of glycemic control among patients with T2D in Eastern Ethiopia. Methods: A cross-sectional study was conducted among 879 adult patients with T2D on follow-up at two public hospitals in Harar. Data were collected through interviews, physical measurements, and record reviews. The level of glycemic control was determined from the three consecutive fast plasma glucose (FPG) measurements. A mean value of FPG measurements falls in the normal range (80–130 mg/dL) was considered as optimal glycemic control otherwise the mean FPG that is below or above the normal range (<80 mg/ dL or >130 mg/dL) was defined as suboptimal glycemic control. Descriptive statistics were used to summarize the data while a linear regression model was used to find out the correlates of glycemic control. A beta coefficient and a 95% CI reported associations. The statistical significance was declared at a p-value of ≤0.05. Results: The mean age of patients with T2D was 52.7(±13.3) years. The mean FPG was 172 ±56mg/dl. Suboptimal glycemic control was found in 76% (95% CI:73.41,79.04) of patients with T2D. In a multivariable linear regression, khat chewing (β= 6.12; 95%CI:1.55,8.69); triglycerides (β= 0.56; 95% CI:0.41.48,0.65), comorbidity(β=5.29;95%CI:1.39,9.13), and poor level of self-care practices (β=5.43;95%CI: 1.41, 6.46) showed significant correlation with glycemic control. Conclusions: This study found that about three-fourths of patients with T2D had suboptimal glycemic control. Khat chewing, comorbidity, and poor level of self-care practices were independently correlated with glycemic control. Thus, suppressing glycemic levels through appropriate treatment, and strict diabetes self-care practices including avoidance of Khat chewing are useful approaches to attaining glycemic target that subsequently reduces cardiovascular risks.